Counteracting the Results of Natural Disasters in the Region of South Asia - Piepiora, Zbigniew (Przeciwdziałanie skutkom katastrof naturalnych w regionie Azji Południowej, 2010)
The number of natural disasters increases in the region of South Asia. Their occurrence often causes death or injuries of many people. Destroying the public and private property is the result of the natural disasters which contribute to boosting the costs of living and to deteriorating the quality of life in the examined region. In the face of these alarming facts it is necessary to make the analysis of these kind of phenomena and of counteracting their results. It is the aim of this article.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 134, s. 102-114
Keywords: natural disaster; South Asia; counteracting; results